Increase reliability of the automated manufacturing systems of a timber industry complex - Orikhovskyy , Roman (Forestry, Forest, Paper and Woodworking Industry, 2007)
The problems of usage of modern methods of definition of reliability of the equipment for the sanction of problems of increase of efficiency of operation of the automated manufacturing systems on firms of a timber industry complex are esteemed.